FieldREG Measurements in Egypt: Resonant Consciousness at Sacred Sites - Nelson, Roger D. (Journal of Scientific Exploration, 2024)
Over a two-week period, various “sacred sites” in Egypt were visited by a group interested in the spiritual qualities of the ancient temples, pyramids, and tombs. The group engaged in informal ceremonies, including chanting and meditation, to pay respect to the sacred sites of the ancient Egyptians. A portable random event generator and palmtop computer were used to generate and record ongoing random sequences accompanied by a time-stamped computer index and onsite notes of relevant observations and activities. Pre-planned hypotheses predicted anomalous deviations of the sequences during visits to the sacred sites, including the inner sanctum or Holy of Holies in each temple and all the interior chambers of the pyramids. A further prediction was made that resonance- or coherence-building activities of the group, including chanting and meditation in these special locations, would also correlate with anomalous deviations. Both formal hypotheses were confirmed with a combined associated probability of 2.7x10^-6. Other categories of data provided context and helped to distinguish the sources of the anomalous effects.